2014
DOI: 10.1007/s12028-014-9977-8
|View full text |Cite
|
Sign up to set email alerts
|

Brain Iron Metabolism and Brain Injury Following Subarachnoid Hemorrhage: iCeFISH-Pilot (CSF Iron in SAH)

Abstract: Objectives To explore the relationship between levels of non-protein bound iron in cerebrospinal fluid and the development of early brain injury in patients with aneurysmal SAH. Design Prospective observational cohort pilot study. Setting Neurointensive care unit of an academic, tertiary medical center Patients Patients admitted with aneurysmal subarachnoid hemorrhage Hunt and Hess grades 2 to 4 requiring ventriculostomy insertion as part of their clinical management. Interventions None. Measurements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 42 publications
1
37
0
Order By: Relevance
“…Fibrin cleaved from fibrinogen has been reported to play a potential role in neuroinflammation and microglial activation (Lim-Hing and Rincon, 2017). Iron, degraded from hemoglobin, is one of most important factors among various components for hemorrhagic stroke-induced BBB hyperpermeability (Hua et al, 2007;Gomes et al, 2014), which is supported by ICH/SAH studies revealing alleviated brain edema with administration of the iron chelator, deferoxamine (Lee et al, 2010;Okauchi et al, 2010;Yu et al, 2014), or a heme oxygenase (HO) inhibitor (Wagner et al, 2000;Han et al, 2018). HO plays a critical role in the degradation of heme and the release of free ferrous iron (Kamat et al, 2019).…”
Section: Mechanisms Of Bbb Dysfunction Secondary To Hemorrhagic Strokementioning
confidence: 99%
See 1 more Smart Citation
“…Fibrin cleaved from fibrinogen has been reported to play a potential role in neuroinflammation and microglial activation (Lim-Hing and Rincon, 2017). Iron, degraded from hemoglobin, is one of most important factors among various components for hemorrhagic stroke-induced BBB hyperpermeability (Hua et al, 2007;Gomes et al, 2014), which is supported by ICH/SAH studies revealing alleviated brain edema with administration of the iron chelator, deferoxamine (Lee et al, 2010;Okauchi et al, 2010;Yu et al, 2014), or a heme oxygenase (HO) inhibitor (Wagner et al, 2000;Han et al, 2018). HO plays a critical role in the degradation of heme and the release of free ferrous iron (Kamat et al, 2019).…”
Section: Mechanisms Of Bbb Dysfunction Secondary To Hemorrhagic Strokementioning
confidence: 99%
“…However, according to the mechanisms of BBB dysfunction and ferroptosis discussed above, the role of ferroptosis on BBB damage warrants more attention. We have mentioned above with sufficient evidence that iron, when degraded from hemoglobin, has a critically important role in BBB hyperpermeability after hemorrhagic stroke, and decreasing iron content through various methods significantly reversed the brain edema (Wagner et al, 2000;Hua et al, 2007;Gomes et al, 2014;Yu et al, 2014). The key point of this problem lies in the poor understanding regarding the exact mechanism of iron overload-induced BBB hyperpermeability.…”
Section: Crosstalk Between Bbb Dysfunction and Pcds In Hemorrhagic Stmentioning
confidence: 99%
“…148 This increase is accompanied by a significant upregulation in HO-1 levels in microglia and neuronal death via oxidative DNA injury 149. A pilot study in human patients suggested a causal relationship between free iron in the CSF following SAH and brain injury 150. Indeed, suppression of hepcidin (and thus inhibition of FP1 internalisation) attenuated brain damage following experimental SAH, suggesting the importance of intracellular iron accumulation 29.…”
Section: Subarachnoid Haemorrhagementioning
confidence: 99%
“…Free heme released into the subarachnoid space during SAH is metabolized by HO-1, releasing iron (Fe 2+ ), biliverdin, and carbon monoxide (CO) (Kikuchi, Yoshida, & Noguchi, 2005).Free iron is thought to cause cell membrane damage via free radicals and the Fenton reaction (Loftspring, 2010). Previous studies have shown a causal relationship between free iron and brain injury following SAH (Gomes et al, 2014).…”
Section: Heme Ox Yg Ena S E (Ho)mentioning
confidence: 99%